Parity and Duration of Labor Affects the Risk of Urinary Retention in post C-Section Patients - Nurullah, Yulia I. (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To determine the rate of urinary retention cases and contributing risk factors in Department of Obstetrics and Gynecology Dr. Mohammad Hoesin Hospital (RSMH), Palembang. Methods: The study conducted on 111 patients who met our study criteria. After CS, urinary catheter were inserted for 24 hours, and then it was opened for 6 hour, after that patients were asked to urinate spontaneously, then we examined the residual urine volume with transvaginal ultrasound. If residual urine volume post CS was >200 ml, it categorized as urinary retention. Result: During the follow up we found that the rate of urinary retention after CS was 3.6% (4 subject). All subject has a covert urinary retention. Factors contribute to post CS urinary retention was duration of labor and parity. The mean of labor duration in group with urinary retention is 8.75±13.04 hour, and 7.55±7.28 hour in the normal group (p = 0.003 RP= 106.00 CI 95%= 6.587-1705.778). All case with urinary retention were primipara (p = 0.045). Conclusion: Our study found that the rate of post CS urinary retention was 3.6%. Risk factors for post CS urinary retention were duration of labor more than 24 hours and primipara. [Indones J Obstet Gynecol 2013; 37-1: 46-50] Keyword: caesarean section, residual urine, urinary retention